An analytical study of quantum walk through glued-tree graphs. (12th August 2015) - Li, Zhi-Jian; Wang, J B
Abstract: In this paper, we analytically investigated the transmission properties of continuous time quantum walks through two types of glued-tree graphs. By mapping the glued-tree graphs onto a non-uniform lattice line, we obtained their bound eigen-energies, which provided a clear and quantitative understanding of the associated resonant transmission behaviours. We also observed interesting zero-mode resonant transmissions, which correspond to zero-energy bound states, for both types of glued-tree graphs with classical Markov transition matrix parameters. By changing the system parameters at the glued nodes, we are able to control the position of the resonant tunnelling peaks.